Creating a 21st Century National Innovation System for a 21st Century Latvian Economy - Watkins, Alfred; Agapitova, Natalia (World Bank, Washington, D.C., 2013)
The Latvian economy made great strides in recovering from the economic shock of the early transition and the adverse aftereffects of the 1998 Russian financial crisis. Nevertheless, Latvia faces serious challenges to its future growth and prosperity despite these impressive achievements and the outward appearance of macroeconomic stability and economic progress. A wide variety of recent studies suggest that the Latvian economy is not particularly competitive and, even more worrisome, they indicate that Latvia is not well positioned to gain ground in the race for global competitiveness, prosperity, and rising standards of living. Most of Latvia's growth to date has come from one-off gains generated by structural reforms, privatization, and reallocating resources, not inexhaustible reservoirs of growth. Latvian enterprises will be able to sustain economic growth and create high wage jobs only by becoming internationally competitive, innovating, accumulating new knowledge and technology, and finding a high value added niche in the European and global division of labor. This paper is designed to help Latvian leaders develop a clear diagnosis of the innovation and competitiveness challenges facing Latvia as it prepares to enter the EU and, more important, design and implement policies and programs to ensure that Latvia reaps the maximum possible benefits from EU structural funds. Section II analyzes the current structure of Latvia's production, imports, and exports. Section III uses data from a number of competitiveness reports to benchmark Latvia's current progress against a number of comparator countries and to pinpoint Latvia's strengths and weaknesses as an innovative economy. Section IV offers a detailed list of potential policies and programs that could improve the competitiveness of Latvian enterprises and the efficiency of the Latvian National Innovation System. The recommendations include specific policies and programs to improve (1) the production of knowledge in Latvia, (2) the commercialization of technology produced by Latvian scientists, small companies, and research institutes, and (3) local firms' capacity to absorb, adapt, and adopt existing knowledge produced outside Latvia for use inside Latvia.